Towards a “Freiburg Model” of housing for the common good? Fostering collaborative housing in urban development - Schmid, Benedikt; Fricke, Carola; Zengerling, Cathrin (2024)
Abstract: As the social and ecological costs of capital-driven housing markets become increasingly apparent, local governments are (re)establishing collaborations with housing organizations that prioritize affordability and sustainability over profits. This hesitant re-orientation, however, takes place under conditions of strained local budgets and the inscription of market principles into existing public policies and planning law. In this article, we develop an interdisciplinary perspective on the interplay between municipal housing policies, planning and legal frameworks, and collaborative housing organizations in the district development project “Kleineschholz” in Freiburg, Germany. Promoted by the local government as being 100% oriented towards the common good, multiple elements of the project are geared towards community involvement and a close dialogue between public bodies and housing organizations. At the same time, the local government and administration navigate divergent interests within and outside municipal institutions, multi-level legal frameworks, financial constraints, as well as institutional routines. We trace how the project’s common-good orientation is integrated into the co-productive process between housing policy, planning law, and collaborative housing groups. Our analysis centers on the process of concept-based tendering which is a key municipal lever for the project’s orientation towards the common good. Moving beyond the situated district of Kleineschholz, we outline the potentials and challenges of translating an orientation towards the common good into collaborative district development, against the background of present political and legal frameworks.